Effect of flange section on shear capacity of triangular profiled web girder using finite element method - Nur Narith Shuhada Shapril (School of Environmental Engineering, University Malaysia Perlis, 2016)
To study the buckling behavior and the strength of triangular profiled web girder. To study the flange geometry configuration. To investigate the imperfection sensitivity due to shear. To compare the enhancement of triangular profiled to the conventional flat plate girder.